STUDI DESKRIPTIF PEMBELAJARAN MUSIK REKORDER PADA SISWA KELAS VII-1 SMP NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN - Syahrial, Harvan Nur; Erfan, Erfan; Hadi, Harisnal (SENDRATASIK UNP, 2019)
AbstractÂ The purpose of this study is to describe the recorder music learning on class VII-1 students at SMP Negeri 2 Lengayang, Pesisir Selatan Regency. The theoretical framework used in this study relates to study and learning, learning the musical art and Recorder Music Learning in Junior High School (SMP). This type of study was a qualitative with using descriptive analysis method. The research instrument was the researcher and it was assisted by data collection tools such as observation note, interview guidelines, and document note. The types of data were primary and secondary data. The analysis techniques were done by collecting, reducing, and concluding. The result shows that the recorder music learning on class VII-1 students in semester 2 was the learning that was not in accordance with the syllabus and lesson plans that were guided / made by the teacher based on Curriculum 2013. It is because the recorder learning that should be carried out by the students is in the form of a kind of music ensemble learning, it is still carried out in the recorder music learning individually by the students. Even though the students are in the same class, each of them has different ways and abilities in practicing to play the game of recorder music. On the other hand, the teacher has also reasoned that directly providing the recorder ensemble to students will be difficult because the basic ability of playing the recorder individually is still weak.Â Keywords: recorder music learning, musical art, cultural art